Pengaruh Motivasi, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Dinas Pekerjaan Umum Sumber Daya Air Dan Penataan Ruang Provinsi Jawa Tengah) - Maheswari, Dinda Putri; Isnowati, Sri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
These research was conducted towards determine affect of worker motivation, compensation, and discipline on worker performance. The butt of this research are worker of the Dinas Pekerjaan Umum Sumber Daya Air dan Penataan Ruang Provinsi Jawa Tengah. Data aggreegation was carried out using a questionnaire and the sampling method using was a random sampling of 74 respondents. The data explanation approach former is validity test, reliability test, multiple linear regression analysis test, F test, coefficient of determination test (R2), and t test put on SPSS version 25. The result of these study indicate it: a. motivation own a regression value of 0,134 with significance of 0,037; b. compensation own a regression value of 0,281 with significance of 0,000; c. work dicipline own a regression value of 0,691 with significance of 0,000. Those shall get deduce motivation, compensation, and work discipline together possess significant positive influence under worker performance